1956
DOI: 10.1111/j.2164-0947.1956.tb00489.x
|View full text |Cite
|
Sign up to set email alerts
|

SECTION OF PSYCHOLOGY: EMOTIONAL BEHAVIOR AND THE NERVOUS SYSTEM*

Abstract: 601Investigations of the various physiological and psychological conditions upon which the organization of emotional behavior depend have long occupied the attention of biological scientists concerned with the broad problem of brain-behavior relationships. The pioneering efforts of men like Geltz! and Sherrington 2 more than half a century ago effectively set the stage for the important contributions of Cannen,3 Dusser de Barennef and, more recently, Bards and Kluver,6 elucidating the role of forebrain structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1957
1957
1964
1964

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Available evidence Brady, 1956;Brady, 1958a;Brady, 1958b;Delgado et al, 1954;Miller, 1958;Olds, 1958a;Olds, 1958b;Olds, 1955;Olds, 1956a;Olds, 1956b;Olds, 1958c;Olds et al, 1956;Olds et al, 1954;Sidman et al, 1955), would seem to indicate that a wide range of conditions can affect the reinforcing properties of an intracranial electrical stimulus and that the locus of the stimulated area contributes prominently to the observed behavioral effects. The present study, however, suggests that a careful analysis of the electrophysiological events consequent upon brain stimulation may provide important additional leads to the necessary and sufficient conditions for the maintenance of such electrical self-stimulation behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available evidence Brady, 1956;Brady, 1958a;Brady, 1958b;Delgado et al, 1954;Miller, 1958;Olds, 1958a;Olds, 1958b;Olds, 1955;Olds, 1956a;Olds, 1956b;Olds, 1958c;Olds et al, 1956;Olds et al, 1954;Sidman et al, 1955), would seem to indicate that a wide range of conditions can affect the reinforcing properties of an intracranial electrical stimulus and that the locus of the stimulated area contributes prominently to the observed behavioral effects. The present study, however, suggests that a careful analysis of the electrophysiological events consequent upon brain stimulation may provide important additional leads to the necessary and sufficient conditions for the maintenance of such electrical self-stimulation behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Following the original observations by Olds and Milner that localized brain stimulation could serve as a reward for lever pressing (Olds et al, 1954), several reports have described interaction effects involving electrical self-stimulation of selected brain areas and a wide variety of behavioral, physiological, and anatomical factors Brady, 1956;Brady, 1958a;Brady, 1958b;Brady, Boren, Conrad & Sidman, 1957;Lilly, 1958;Miller, 1958;Olds, 1958a;Olds, 1955;Olds, 1956a;Olds, 1956b;Olds, 1958b;Olds, Killan & Bach-y-Rita, 1956). However, surprisingly little attention has been directed toward an analysis of the interrelationships between the physiological events associated with self-stimulation and the behavior of the self-stimulating animal.…”
mentioning
confidence: 99%
“…Several recent reports have described interaction effects involving electrical self-stimulation of selected brain areas and a wide variety of physiological and psychological phenomena. Experimental demonstrations of positively reinforcing effects produced by inlracranial self-stimulation in the rat (Olds & Milner, 1954), cat (Brady, 1956), and monkey (Brady, 1958b) have now been extended to an analysis of relationships involving electrode location (Olds, 1956), stimulus intensity (Reynolds, 1958), schedules of reinforcement (Sidman, Brady, Boren, Conrad, & Schulman, 1955), food and water deprivation (Brady, Boren, Conrad, & Sidman, 1957), sex hormones (Olds, 1958a), drugs (Olds, Killam, & Bach-y-Rita, 1956), and satiation effects (Olds, 1958b). Significantly, however, emotional or affective changes related to positively rewarding brain stimulation have received little direct experimental attention.…”
mentioning
confidence: 99%
“…Recent reports of the rewarding properties of electrical brain stimulation (Olds & Milner, 1954;Brady, 1956;Brady, 1958) suggest an interesting approach to the exploration of central-nervous-system participation in such timing behavior. It has been demonstrated that stable lever pressing on several different schedules of reinforcement can be maintained in laboratory animals for an intracranial electrical stimulus in selected areas of the brain without any other reward (Sidman, Brady, Boren, Conrad, & Schulman, 1955).…”
mentioning
confidence: 99%